Immunological markers of frailty predict outcomes beyond current risk scores in aortic stenosis following transcatheter aortic valve replacement: Role of neopterin and tryptophan. (March 2016) - Csordas, Adam; Fuchs, Dietmar; Frangieh, Antonio H.; Reibnegger, Gilbert; Stähli, Barbara E.; Cahenzly, Martin; Nietlispach, Fabian; Maier, Willibald; Maisano, Francesco; Binder, Ronald K.; Liebetrau, Christoph; Kim, Won-Keun; et al.
Abstract: Background: Frailty and associated comorbidities are often prohibitive surgical risk factors in symptomatic severe aortic stenosis. Transcatheter aortic valve replacement (TAVR) is a viable treatment option for such patients. However, biomarkers providing a precise estimate of individual vulnerability and hence pre-interventional risk for mortality are not available in this heterogenous patient population. Neopterin, a pteridine synthesized by activated macrophages, has been associated with prevalent frailty in elderly patients. Moreover, immune activation-mediated tryptophan degradation has been suggested to reflect frailty and reduced life expectancy in diverse chronic disease states. Methods: We thus prospectively investigated a total of 185 patients undergoing TAVR and measured neopterin, kynurenine, tryptophan, tyrosine and phenylalanine levels at baseline and at day 1–3 post intervention. Royston-Parmar proportional hazards models were employed relating biomarkers to all-cause mortality. Results: In bivariate analysis adjusted for EuroSCORE II, belonging to the upper quartile of neopterin (HR 5.7, 95% CI: 2.0–16.5, P < 0.01), KTR (HR 3.1, 95% CI: 1.1–8.5, P = 0.02) and Phe/Tyr ratio (HR 2.8, 95% CI: 1.0–7.7, P = 0.03) emerged as independent predictors of mortality. A similar finding on neopterin and KTR was obtained in 207 patients of an independent external validation cohort. Conclusions: Increased immune activation and associated tryptophan degradation serve as hallmarks of frailty underscoring the prognostic role of baseline inflammation for outcome in patients with severe aortic stenosis undergoing TAVR, and thus may provide a future therapeuthic target in this elderly patient population.